ANALYSIS OF MODERN METHODS FOR OIL SLUDGE PROCESSING (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The problem of the negative impact on the environment of accumulated waste generated during the production, transportation, and storage of oil and petroleum products has not yet been resolved. As a result of the migration of harmful substances, environmental pollution occurs. It should be noted that all processes of transformation of NS hydrocarbons are activated in a hot climate - due to a decrease in viscosity and an increase in the reaction rate.